Thermodynamic Properties of Two Cinnamate Derivatives with Flavor and Fragrance Features - Vera L. S. Freitas; Carlos A. O. Silva; Maria D. M. C. Ribeiro da Silva (Liquids, 2024)
The standard molar enthalpies of formation in the liquid phase for ethyl (E)-cinnamate and ethyl hydrocinnamate, two cinnamate derivatives with notable flavor and fragrance characteristics, were determined experimentally using combustion calorimetry in an oxygen atmosphere. To derive the gas-phase enthalpies of formation for these derivatives, their enthalpies of vaporization were measured using a high-temperature Calvet microcalorimeter and the vacuum drop microcalorimetric technique. Additionally, a computational analysis employing the G3(MP2)//B3LYP composite method was conducted to calculate the gas-phase standard enthalpies of formation at T = 298.15 K for both compounds. These findings enabled a detailed assessment and analysis of the structural and energetic effects of the vinyl and ethane moieties between the phenyl and carboxylic groups in the studied compounds. Considering the structural features of ethyl (E)-cinnamate and ethyl hydrocinnamate, a gas-phase enthalpy of hydrogenation analysis was conducted to explore their energetic profiles more thoroughly.